Analisis Kebijakan Rencana Pembangunan Kereta Gantung Seruni Point-Gunung Bromo dalam Mendukung Peraturan Presiden Nomor 80 Tahun 2019 - Fasya, Muhammad Najih (Jurnal Ilmiah Pariwisata, 2024)
The cable car development plan is one of the main projects proposed by the Governor of East Java, Dra Hj. Khafifah Indar Parawansa, M.Sc to accelerate the construction of the TN BTS, including through the construction of a cable car facility which will be an attraction for tourists to enjoy the sunrise and sunset views in the TN BTS area. The development of a cable car has the potential to bring commercial benefits for both the community and the government. The purpose of this study is to analyze various tourism policies that support the plan to build the Seruni Point-Bromo cable car. Based on the policy analysis, conformity has been found between the cable car development plan and various planning and development policy documents. The plan to build a cable car in a strategic tourism area has the potential to drive investment so that it will trigger economic growth. The development of a cable car can create a new tourist attraction that has a different type in an effort to capture new market opportunities. Keywords: content analysis, tourism policy